2016
DOI: 10.1155/2016/7830768
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Polymerization Functions in Hypersensitive Response and Accumulation of H2O2in Wheat Induced by the Stripe Rust

Abstract: The plant cytoskeleton, including microtubules and microfilaments, is one of the important factors in determining the polarity of cell division and growth, as well as the interaction of plants with invading pathogens. In defense responses of wheat against the stripe rust (Puccinia striiformis f. sp. tritici) infection, hypersensitive response is the most crucial event to prevent the spread of pathogens. In order to reveal the effect of microtubules on the hypersensitive cell death and H2O2 accumulation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…ROS and MTs have a close but complex relationship in plants. For instance, both ROS‐induced microtubule depolymerization (Yao et al ) and MTs‐resulted ROS accumulation (Wang et al ) were reported in the previous studies. In addition, Zhu et al () demonstrated a positive H 2 O 2 amplification loop regulated by MAP65, a microtubule‐associated protein.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…ROS and MTs have a close but complex relationship in plants. For instance, both ROS‐induced microtubule depolymerization (Yao et al ) and MTs‐resulted ROS accumulation (Wang et al ) were reported in the previous studies. In addition, Zhu et al () demonstrated a positive H 2 O 2 amplification loop regulated by MAP65, a microtubule‐associated protein.…”
Section: Discussionmentioning
confidence: 80%
“…For example, using diphenylene iodonium (DPI) alone or together with exogenous H 2 O 2 , Yao et al () showed that NADPH oxidase‐mediated ROS accumulation was responsible for MT‐depolymerization in plant defense against Verticillium dahlia , a soil‐borne pathogen. Wang et al (), however, reported that MTs were related to hypersensitive response and H 2 O 2 accumulation in wheat induced by the stripe rust. Furthermore, Zhu et al () showed that ZmMAP65‐1a, a microtubule‐associated protein in maize, positively regulated H 2 O 2 amplification and enhanced BR‐induced antioxidant defense.…”
Section: Introductionmentioning
confidence: 99%
“…MTs facilitate the transport of immunity‐related proteins to the apoplast (Guo et al ., ) and are partly responsible for the accumulation of H 2 O 2 and the induction of HR‐PCD in response to an avirulent CYR23 strain of Puccinia striiformis f. sp. tritici in wheat (Wang et al ., ). MICROTUBULE‐ASSOCIATED PROTEIN 65‐3 (MAP65‐3) binds MTs and regulates MT depolymerization (Stoppin‐Mellet et al ., ; Struk & Dhonukshe, ), and mediates defense against downy mildew and powdery mildew through the regulation of SA and JA signaling pathways (Quentin et al ., ).…”
Section: The Cytoskeleton In Plant–microbe Interactionsmentioning
confidence: 97%
“…The HR is a local cell death response at the site of infection that involves highly dynamic reorganization of host cells and often manifests as localized programmed cell death (PCD), which effectively prevents the spread of biotrophic pathogens (Balint‐Kurti, 2019; Higaki et al, 2011; Liu et al, 2005). An HR typically occurs during successful defence in host plants, usually leaving only small necrotic spots (Wang et al, 2016). Wang et al (2009) observed that Arabidopsis thaliana with delayed HR showed compromised resistance to Pseudomonas syringae pv.…”
Section: Introductionmentioning
confidence: 99%